Kapabilitas Managerial Kepala Sekolah dalam Implementasi Pembelajaran Tahfiz - Muhammad Wahyu Amirulloh; Muhammad Najib (DAARUS TSAQOFAH Jurnal Pendidikan Pascasarjana Universitas Qomaruddin, 2023)
The managerial ability of the principal in the implementation of learning is very important in the school. The role of the principal in the school is to be a managerial, supervisor, and evaluator. In the implementation of learning, the principal must be able to encourage learners, including the implementation of tahfiz learning. In the current era, Qur'anic learning education is also very necessary in producing a generation with Qur'anic morals. Therefore, school principals need to have good skills in managing the implementation of tahfiz learning. The objectives of this study are (1) To determine the managerial capabilities of female principals in tahfiz learning at Assa'adah High School. (2) To know the implementation of tahfiz learning at Assa'adah High School. (3) To find out the principal's leadership strategy in managing tahfiz learning at Assa'adah High School. The approach used is a qualitative approach with a type of descriptive research. The data sources used in this study were in-depth interview methods, observation and documentation. In-depth interviews are used to search for data by conducting a structured dialogue. Observations are made to find data by looking directly at what is happening in the field. The documentation is used to find data by taking pictures of the actual situation that occurred. The results of this study show that: (1) the managerial capabilities of female school principals are to manage, supervisor, and evaluator. (2) the implementation of class X tahfiz learning is very good. In one week there are already their own methods every day, ranging from moroja'ah, addition, and deepening of knowledge. (3) The strategy carried out by the principal in the implementation of tahfiz learning is in the form of motivation and supervision of students, both at home and at home.